Salmonella enterica serovar enteritidis peritonitis with spontaneous intestinal perforation in an immunocompetent patient - Hélias, Marion (BMJ Case Rep, 2019)
Few data reported non-typhoidal Salmonella peritonitis in immunocompromised patients. We reported the case of a man without immunosuppression or predisposing factor, who developed Salmonella enterica serovar Enteritidis peritonitis with spontaneous intestinal perforation. After emergent surgery, the patient was transferred to intensive care unit (ICU) because of respiratory, renal and haemodynamic failures. When S. enterica serovar Enteritidis was identified, antibiotics were de-escalated for ceftriaxone and metronidazole for 5 days. No immunosuppression was found. Evolution was favourable, and the patient has been discharged from the ICU on day 8. The originality of this case arises from a perforation peritonitis secondary to S. enterica without any immunosuppression. In absence of non-Typhi Salmonella data, we treated this patient as a typhoid perforation: surgical treatment, antibiotic association and supportive care.